2017
DOI: 10.3389/fnhum.2017.00520
|View full text |Cite
|
Sign up to set email alerts
|

Resting Heart Rate Variability, Facets of Rumination and Trait Anxiety: Implications for the Perseverative Cognition Hypothesis

Abstract: The perseverative cognition hypothesis (PCH) posits that perseveration, defined as the repetitive or sustained activation of cognitive representations of a real or imagined stressor, is a primary mechanism linking psychological (or stress) vulnerability with poor health and disease. Resting vagally mediated heart rate variability (vmHRV) is an important indicator of self-regulatory abilities, stress vulnerability and overall health. Those with lower resting vmHRV are more vulnerable to stress, and thus more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 48 publications
2
41
1
Order By: Relevance
“…Rumination, as a type of MW which tends to be fixed on a single theme or topic and is marked by a high degree of automatic constraints [ 33 ], attenuates the normal variation in speaker’s pitch in relation to a conversation partner’s pitch. This falls in line with research that has associated rumination with reduced variability in physiological cues, including heart rate variability, which suggests rumination is associated with higher levels of cognitive inflexibility [ 17 , 95 97 ]. Our study is novel in that it demonstrates that rumination not only predicts reduced variability in physiological cues, it also attenuates pitch imitation which occurs during interactions.…”
Section: Discussionsupporting
confidence: 88%
“…Rumination, as a type of MW which tends to be fixed on a single theme or topic and is marked by a high degree of automatic constraints [ 33 ], attenuates the normal variation in speaker’s pitch in relation to a conversation partner’s pitch. This falls in line with research that has associated rumination with reduced variability in physiological cues, including heart rate variability, which suggests rumination is associated with higher levels of cognitive inflexibility [ 17 , 95 97 ]. Our study is novel in that it demonstrates that rumination not only predicts reduced variability in physiological cues, it also attenuates pitch imitation which occurs during interactions.…”
Section: Discussionsupporting
confidence: 88%
“…There are indications that negative stress indicators more strongly predict level of vmHRV than positive, competence measures (Silvia, Jackson, & Sopko, 2014; P. Williams et al, 2017). This may represent another explanation why selfcompassion associates stronger with higher vmHRV than mindfulness in our study, due to the greater focus on suffering in self-compassion.…”
Section: Self-compassion Relating To Vmhrv Beyond Mindfulnessmentioning
confidence: 51%
“…A number of studies also showed that HRV biofeedback reduces self-reported stress and anxiety with a large effect size that does not seem to be limited to a clinical level of anxiety [16]. Based on previous findings, linking high HRV to better response inhibition and emotion regulation [33][34][35], Mather & Thayer (2018) hypothesized that HRV biofeedback enhances interactions in emotion regulatory brain regions. Core brain regions that are involved in the experience and perception of emotions are the anterior insula, the amygdala, and the cingulate cortex [36].…”
Section: Discussionmentioning
confidence: 99%